Genre Analysis of Conclusion Chapters in Master’s TEFL Thesis - Amaliah, Ayu; Dalimunte, Ahmad Amin; Chaniago, Anisah Firly; Syafitri, Lia Nata (Pioneer: Journal of Language and Literature, 2024)
Writing a thesis in English is challenging for students, especially Indonesian Master's students for whom English is not their first language. Inherently, each chapter presents challenges to address when organizing a thesis. One of the crucial parts of the thesis is the conclusion chapter. It serves as a summary and a place to express suggestions and potential lines for further study. Thus, this study examined how Indonesian students wrote conclusion chapters of TEFL Master's theses. A total corpus of 3897 words was generated as the present study's data. Based on Chen & Kuo (2012) as the analytical framework of the present study, we found that move 2 step 1 (summarizing the study) was frequently used. Both move 1 (introducing the conclusion) and move 3 (evaluating) are obligatory. We also found optional moves and steps providing supporting and complementary roles: Move 4, step 2, and Move 3, step 1. These findings indicate that Indonesian master's students in the TEFL program used the conclusion writing of genre-based method characterized by the ability to adapt to conventional genre-framework and add additional steps. Understanding and using these variations can help Indonesian students craft concluding chapters that demonstrate scholarly engagement and the academic rigor of their study.